Taylor Polynomial Approximation and Adaptive Passivity-Based Control Applied to the Level Regulation of a Conical Tank - Travieso-Torres, J (Wiley-Blackwell, 2017)
The techniques of Taylor polynomial approximation (TPA) and adaptive passivity-based controller (APBC) are combined in this study and applied to the level regulation of a conical tank. The design and comparative experimental results with a classical PI controller are presented. After combining these two approaches a robust adaptive controller named TPA–APBC, which is simpler than the classical APBC and PI controller, is obtained. This new TPA–APBC preserves the stability of the overall system after assuming that the nonlinear system is unknown and that it can be suitably represented by a first-order linear model with unknown parameters. © 2017 Chinese Automatic Control Society and John Wiley & Sons Australia, Ltd